Evaluation of fundus first laparoscopic cholecystectomy in an obscured calot triangle: outcomes - Jalal Namq, Amanj; Muhammed Dewana, Azhy; Saeed Ahmed, Baderkhan; Ahmed Aziz, Sherwan; Shalli, Kawan (Diyala Journal of Medicine, 2024)
Background: A fundus first laparoscopic cholecystectomy when performed by an experienced surgeon, provides the same level of safety and durability as an open cholecystectomy. When Calot's triangle cannot be safely dissected during laparoscopic cholecystectomy a rescue treatment is advised. Current revisions stress the importance of intraoperative observations in helping surgeons make a rescue decision and minimize additional harm. Objective: To examines the fundus-first strategy in laparoscopic cholecystectomy in an indistinct Calot's triangle and the patient's clinical outcome. Patients and Methods: This is a prospective study that was done in Rizgary Teaching Hospital from January 1st, 2020 to December 31st, 2022, on 68 cases who underwent laparoscopic cholecystectomy where Calot’s triangle was difficult to distinguish during the operation. Fundus: first dissection of the gall bladder down to the infundibulum and after safe ligation of the gall bladder stump and good hemostasis of the liver bed, the gallbladder is removed via a 10-mm port. This research looked at the duration of operation, postoperative pain, rate of conversion to open surgery and duration of the hospital stay. Results: Among 68 cases of fundus first laparoscopic cholecystectomy most of the patients were female 45(66.17%) and 23(33.82%) were male, majority of cases were between 31 and 50 years old, with a mean age of 39±10.44, and the majority of patients were complaining of inflammation with fibrosis at the site of the cystic duct. The duration of operation ranged from 45-60 minutes in 16(23.52%) and 60-80 minutes in 20(29.41%) cases and 130-140 minutes in 2(2.94%) cases. The majority of our cases remained in the hospital and ambulated on day 3-5, and the main hospital stay was 4.68±1.8 days. There was statistical significance in the age distribution with a P-value 0.04. Conclusion: Fundus first laparoscopic cholecystectomy remains a feasible and safe procedure. Surgeon experience and judgement affects the operative time, conversion rate, morbidity and hospital stay in difficult and obscured Calot’s triangle.